THERAPEUTIC MANAGEMENT OF ENDOMETRITIS IN A MARWARI MARE - ARANGASAMY, A; SINGH, J; BANSAL, R S; TANDON, S N (The Indian Journal of Animal Reproduction, 2023)
A case of endometritis in a mare has been presented in this paper.
Keywords: Marwari mare; Endometritis; Treatment; Ultrasound